Information Intelligence, Systems, Technology and Management 5th International Conference, ICISTM 2011, Gurgaon, India, March 10-12, 2011. Proceedings - Dua, Sumeet; Sahni, Sartaj; Goyal, D. P.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 5th International Conference on Information Systems, Technology and Management, ICISTM 2011, held in Gurgaon, India, in March 2011. The 35 revised full papers presented together with 4 short papers were carefully reviewed and selected from 106 submissions. The papers are organized in topical sections on information management, information systems, information technology, healthcare information management and technology, business intelligence, applications, as well as management science and education.
Keywords: Computer science; Computer Communication Networks; Computer software; Data mining; Information systems; Artificial intelligence; Computer Science; Artificial Intelligence (incl. Robotics).; Information Systems Applications (incl.Internet).; Computer Communication Networks; Data Mining and Knowledge Discovery; Algorithm Analysis and Problem Complexity; User Interfaces and Human Computer Interaction